2021
DOI: 10.1177/23333928211002401
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Long-Acting Reversible Contraceptives and Associated Factors Among Reproductive Age Women Attending Governmental Health Institutions for Family Planning Services in Wondo Genet District, Sidama, National Regional State, Southern Ethiopia

Abstract: Background: Utilization of family planning services improves women’s reproductive health outcomes. Long-acting reversible contraceptive (LARCs) methods, in particular, prevent unwanted pregnancy and significantly reduce maternal mortality and morbidity. In Ethiopia utilization of LARCs was very low. Therefore, this study was aimed at assessing the utilization of LARCs and associated factors among reproductive-age women in Wondo Genet District, Southern Ethiopia. Method: Institution based cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Women who have one to two, three to four, and five and above living children had 2.35, 2.98, and 2.82 times higher odds of LARC utilization respectively, as compared to women who have no living children. This finding is consistent with a study conducted in Ethiopia [46,47] Uganda [48], Nigeria [49], Malawi [50], Ghana [51]. The possible reasons might be explained as those women who might have already attained their plan of fertility could use LARCs up to reaching menopause or need to space or limit births may choose effective long acting contraceptive methods from the available options.…”
Section: Discussionsupporting
confidence: 90%
“…Women who have one to two, three to four, and five and above living children had 2.35, 2.98, and 2.82 times higher odds of LARC utilization respectively, as compared to women who have no living children. This finding is consistent with a study conducted in Ethiopia [46,47] Uganda [48], Nigeria [49], Malawi [50], Ghana [51]. The possible reasons might be explained as those women who might have already attained their plan of fertility could use LARCs up to reaching menopause or need to space or limit births may choose effective long acting contraceptive methods from the available options.…”
Section: Discussionsupporting
confidence: 90%
“…The result is lower than that of a study of sexually active women from 26 countries in SSA, which found that 21.73% of them use LARCs [ 12 ]. The rise in the use of LARCs could be attributed to enhanced community mobilisation and understanding of LARCs among women, as well as variations in study time, location, and socio-demographic backgrounds [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The average age of study participants was ranged from 25 (33) to 36(37) years old, with a range of 15-49 years (17,19). Six studies were done in the Oromia region (12,19,23,24,29,31), nine studies in the Amhara region (13-15, 17, 20, 21, 26, 35, 37)and nine studies in SNNP region (16,18,19,22,27,28,33,34,36), and one study each in the Afar region (11), Harari region (30) ,and Addis Ababa city administration (32). Sample size of included studies ranges from 262 (27) to 731(36) and prevalence of LARC users among Ethiopian women over the last ve years ranges from 12.6%(21) to 53.2% (12).…”
Section: Literature Identi Cation and Descriptions Of Studiesmentioning
confidence: 99%